Future Generation Computer Systems - Antonella Longo; Marco Zappatore; Mario A. Bochicchio (Elsevier, 2025)
The collaborative power of ICT systems is a key enabler of social and technological advances providing multiple opportunities for public involvement in participatory activities, thanks to novel paradigms like citizen science and mobile crowd sensing. These paradigms, if applied according to specific methodologies, promise to increase the pervasive observation of urban environmental pollution either directly by human observers, or by means of crowd-sourcing data measurement tasks using sensors in smart phones or other mobile devices. We propose a platform, named Apollon, to enable scientists and others to take part in citizen science projects based on the exploitation of mobile devices. The platform has been implemented and validated in an educational context, in which students participate in urban environmental monitoring activities. In the paper, we describe the platform and the approach developed to produce successful experiments.